2021
DOI: 10.3390/molecules26071924
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Plant Derivate Polyphenols on the Main Protease of SARS Coronavirus 2 and Their Structure–Activity Relationship

Abstract: The main protease (Mpro) is a major protease having an important role in viral replication of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the novel coronavirus that caused the pandemic of 2020. Here, active Mpro was obtained as a 34.5 kDa protein by overexpression in E. coli BL21 (DE3). The optimal pH and temperature of Mpro were 7.5 and 37 °C, respectively. Mpro displayed a Km value of 16 μM with Dabcyl-KTSAVLQ↓SGFRKME-Edans. Black garlic extract and 49 polyphenols were studied for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 50 publications
2
72
1
Order By: Relevance
“…Multiple flavonols derived from black garlic extract (IC50 = 137 ± 10 µg/mL), among whom quercetin and its derivatives showed remarkable efficacies for 3CLpro, likely due to the flavonols' interaction with the 3CLpro substrate-binding site as hypothesized and confirmed by independent researchers [117,118,121]. Others reported that quercetin acts as a competitive inhibitor of the 3CLpro active site and has a dose-dependent destabilizing effect on the thermal stability of the protease [124].…”
Section: Flavonols and Flavanonolsmentioning
confidence: 86%
See 2 more Smart Citations
“…Multiple flavonols derived from black garlic extract (IC50 = 137 ± 10 µg/mL), among whom quercetin and its derivatives showed remarkable efficacies for 3CLpro, likely due to the flavonols' interaction with the 3CLpro substrate-binding site as hypothesized and confirmed by independent researchers [117,118,121]. Others reported that quercetin acts as a competitive inhibitor of the 3CLpro active site and has a dose-dependent destabilizing effect on the thermal stability of the protease [124].…”
Section: Flavonols and Flavanonolsmentioning
confidence: 86%
“…Among these, 3CLpro was investigated against flavonols and flavones more than other subclasses of flavonoids. Tables 1 and 2 summarize the in vitro activities of various flavonoids against SARS-CoV-2 3CLpro, and PLpro reported in the literature, respectively [117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Antiviral Activity Of Flavonoids Against Sars-cov-2 Proteases (3clpro and Plpro)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, phenolics of black garlic also revealed anti-SARS-CoV-2 actions, which is very beneficial given the consumption of this foodstuff derived from the transformation of fresh garlic subjected to high temperatures (>70 °C), has become popular due to its notable antioxidant properties [ 87 ]. In this order of ideas, Nguyen et al [ 88 ] analyzed the capacity of 49 polyphenols present in pure black garlic extract ( Table 2 ) to inhibit the protease activity of the M pro enzyme. The obtained data revealed that this extract can inhibit completely the action of M pro of SARS-CoV-2, presenting an IC 50 value of 137 ± 10 µg/mL.…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19mentioning
confidence: 99%
“…In addition, it has also been evaluated the inhibitory capacity of a mixture of polyphenolics in different concentrations of tannic acid with puerarin, daidzein, and/or myricetin against this protease. It was reported that the most effective combination was a mix of tannic acid (5 µM), puerarin (20 µM), daidzein (20 µM) and myricetin (20 µM), which demonstrated ability to reduce M pro action in the order of 80% [ 88 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19mentioning
confidence: 99%